Comparing the neural correlates of the psychoacoustic and cognitive effects of the linguistic rhythms during listening to the Fatihah Chapter Arabic News - Samhani Ismail
Brain oscillations provide temporal and spatial cues and in order to coordinate distinct neural processes into highly cognitive function, it interacts with the internal and external communication networks. Fatihah Chapter, the first chapter with rhymed syllable, sentence and literary rhythms, found to be endowed with cognitive and psychoacoustical effects. In order to compare experimentally and statistically the neural correlates of the psychoacoustic and cognitive effects, the brainwaves from twenty-eight normal subjects were recorded by EEG-128-channels in three conditions of Resting, Fatihah Chapter recitation by Abdul Basit bin Abdul Samad and Arabic News listening taken from Arabic TV News (Al-Jazeera) and analyzed by Fast Fourier Transform (FFT) to get the power spectrum in canonical frequency bands of Delta, Theta, Alpha, Beta and Gamma by using the Barin Electrical Stimulation Analysis (Besa 6.1). Later, the EEG data were explored by multivariate analysis of Discriminant Analysis, Agglomerative Cluster Analysis and Multi Linear Regression using XLStat statistical packages. Before that, the auditory stimuli were phonetic acoustically investigated by speech analysis tools of Praat and Esection, and the results were than statistisized analyzed bt t-Test to see their significant difference between the linguistic structure of Fatihah Chapter and Arabic News to learn the linguistic rhythms underlying neural entrainment in their listeners. results from acoustic analysis showed, the five of speech elements such as spectrogram, formants, pitch, intensity, rhyming and end rhyming analysis, the Fatihah Chapter brings more energy and is more rhythmic than the Arabic News. results from the quantitative EEG study pertaining to brain oscillations, syncronization and correlation between EEG electrodes, the highly rhythmic scripture which is varied in tones with high energy activates greater neural ensemble in wider brain regions compared to Arabic News. Furthermore, Fatihah Chapter showed greater electrodes correlation with more electrodes involved compared to Arabic News. As a conclusion, frontal-temporal-pariental-occipital areas are involved in perceiving this rhythmic acoustical stimuli in Fatihah Chapter. We speculate that there are some associations od brain ascillations with attention, memory, speech, emotion and behaviour during Fatihah Chapter listening which may eliminate negative emotions besides improving cognition-emotion processing and speech fluency, need to be elucidates in a well controlled neurocognitive experimental setup.